KEMAMPUAN BERBICARA MENGGUNAKAN BAHASA INDONESIA ANAK USIA 5-6 TAHUN TK KERANJIK - Dahlia, Leni; Thamrin, M.; Ali, Muhamad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
Based on the research that has been done and through the results obtained after an analysis of data that: 1) Ability to communicate with children using Indonesian teachers are categorized as